β-arrestin biased signaling is not involved in the hypotensive actions of 5-HT7 receptor stimulation: use of Serodolin - Stephanie W. Watts; Hannah Garver; Severine Morisset-Lopez; Franck Suzenet; Gregory D. Fink (Elsevier, 2024)
The 5-hydroxytryptamine 7 receptor (5-HT7) is necessary for 5-HT to cause a concentration-dependent vascular relaxation and hypotension. 5-HT7 is recognized as having biased signaling, transduced through either Gs or β -arrestin. It is unknown whether 5-HT7 signals in a biased manner to cause vasorelaxation/hypotension. We used the recently described β-arrestin selective 5-HT7 receptor agonist serodolin to test the hypothesis that 5-HT7 activation does not cause vascular relaxation or hypotension via the β -arrestin pathway. Isolated abdominal aorta (no functional 5-HT7) and vena cava (functional 5-HT7) from male Sprague Dawley rats were used in isometric contractility studies. Serodolin (1 nM - 10 μM) did not change baseline tone of isolated tissues and did not relax the endothelin-1 (ET-1)-contracted vena cava or aorta. In the aorta, serodolin acted as a 5-HT2A receptor antagonist, evidenced by a rightward shift in 5-HT-induced concentration response curve [pEC50 5-HT [M]: Veh = 5.2 +/- 0.15; Ser (100 nM) = 4.49 +/- 0.08; p < 0.05]. In the vena cava, serodolin acted as a 5-HT7 receptor antagonist, shifting the concentration response curve to 5-HT left and upward (%10 μM NE contraction; Veh = 3.2 +/- 1.7; Ser (10 nM) = 58 +/- 11; p < 0.05) and blocking relaxation of pre-contracted tissue to the 5-HT1A/7 agonist 5-carboxamidotryptamine. In anesthetized rats, 5-HT or serodolin was infused at 5, 25 and 75 μg/kg/min, iv. Though 5-HT caused concentration-dependent depressor responses, serodolin caused an insignificant small depressor responses at all three infusion rates. With the final dose of serodolin on board, 5-HT was unable to reduce blood pressure. Collectively the data indicate that serodolin functions as a 5-HT7 antagonist with additional 5-HT2A blocking properties. 5-HT7 activation does not cause vascular relaxation or hypotension via the β -arrestin pathway.